EFFICACY OF THE COMBINATION OF RINSKOR AND PENOXSULAM HERBICIDE ON WEEDS CONTROL AND ON GROWTH AND YIELD OF TRANSPLANTING RICE - Akbar Gangsar Gumelar; Abdul Rizal; Siwi Hardiastuti (Jurnal Agrivet, 2018)
This research aims was to determine of rinskor and penoxsulam herbicide combination at appropiate doses and not cause poisoning in rice plants as well as to know the yield of rice paddy plants due to weeds control of rinskor and penoxsulam herbicide combination compared to the usual herbicide used by farmers. This research conducted on the month August to November 2017 in the Pucangan Village, Kartasura Subdstrict, Sukoharjo District. This research used a complete randomized block design with one factor, twelve treatments and repeated 4 times, one the treatment of which is a control. Treatment of rinskor and penoxsulam herbicide combination with dose 750 ml/ha, 1000 ml/ha and 1250 ml/ha as wall as comperative herbicides penoxsulam & sihalofop (500 ml/ha & 800 ml/ha), penoxsulam (800 ml/ha), Natrium byspiripac (300 ml/ha), metil metsulfuron, etil klorimuron, 2,4D natrium (600 ml/ha), metil metsulfuron, 2,4D natrium, etil klorimuron (250+500 ml/ha), fenoksaprop etil dan etoksisulfuron (700 ml/ha), manual and control. Observed result were analyzed, if there is a real difference with a level of 5% will be tested continued using Skott Knott test at 5% confidence level. The result showed that rinskor and penoxsulam herbicide combination, starting with a dose 1000 ml/ha to 1250 ml/ha can control weeds better than other treatments and produce the highest yield of rice crops.Keywords : Herbicide combination, rinskor, penoxsulam, weeds, rice crops